2014
DOI: 10.1038/ncomms4511
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of BET bromodomain epigenetic signalling interferes with the bone-associated tumour vicious cycle

Abstract: The vicious cycle established between bone-associated tumours and bone resorption is the central problem with therapeutic strategies against primary bone tumours and bone metastasis. Here we report data to support inhibition of BET bromodomain proteins as a promising therapeutic strategy that target simultaneously the three partners of the vicious cycle. Treatment with JQ1, a BET bromodomain inhibitor, reduces cell viability of osteosarcoma cells and inhibits osteoblastic differentiation both in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 44 publications
9
117
0
Order By: Relevance
“…9 Thus, BRD4 is a key regulator of the proliferation/apoptosis balance 12,13 by modulating gene expression and plays a critical role in post-DNA damage events. 17 In cancer, BRD4 is a known trigger of the osteogenic factor Runt-related transcription factor 2 expression, 18,19 which was recently associated with PAH lung abnormalities (including proliferation and calcification), 20 and, interestingly, BRD4 inhibition by JQ1 suppressed vascular calcification/atherogenic processes in a hypercholesterolemic murine model. 15 Furthermore, in addition to promoting DNA damage, 17 atherogenic processes 15 and increased proliferation, 12,13 BRD4 is also associated with inflammation, diabetes mellitus, obesity, and metabolic abnormalities, 13 all playing a role in VRDs, and particularly in coronary artery disease (CAD).…”
Section: P Ulmonary Arterial Hypertension (Pah) Is a Vascularmentioning
confidence: 99%
“…9 Thus, BRD4 is a key regulator of the proliferation/apoptosis balance 12,13 by modulating gene expression and plays a critical role in post-DNA damage events. 17 In cancer, BRD4 is a known trigger of the osteogenic factor Runt-related transcription factor 2 expression, 18,19 which was recently associated with PAH lung abnormalities (including proliferation and calcification), 20 and, interestingly, BRD4 inhibition by JQ1 suppressed vascular calcification/atherogenic processes in a hypercholesterolemic murine model. 15 Furthermore, in addition to promoting DNA damage, 17 atherogenic processes 15 and increased proliferation, 12,13 BRD4 is also associated with inflammation, diabetes mellitus, obesity, and metabolic abnormalities, 13 all playing a role in VRDs, and particularly in coronary artery disease (CAD).…”
Section: P Ulmonary Arterial Hypertension (Pah) Is a Vascularmentioning
confidence: 99%
“…Since osteoporosis is an age-related disease, it could be speculated that those age-related changes in epigenetic marks participate in the pathophysiology of the disease [15]. Recent studies demonstrated JQ1 (a bromodomain inhibitor developed by the Structural Genomic Consortium) to suppress inflammation by a reduction of the inflammatory cytokine release, bone destruction by the inhibition of osteoclast maturation and bone formation by the inhibition of osteoblast maturation [15,16]. The latter activity makes its use for the treatment of osteoporosis questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Besides bone formation, bone homeostasis is maintained by the balance between osteoblastic bone formation and osteoclastic bone resorption, whereas the growth of long bones is from endochondral ossification of chondrocytes derived from cartilage (15). Previous studies have shown that BET inhibitors may affect osteoclastogenesis (14) and the bone-associated tumor vicious cycle (13). In this study, we demonstrated BET inhibitors as repressors of chondrogenesis.…”
Section: Discussionmentioning
confidence: 66%
“…In addition to this, multiple other BET inhibitors have been well studied and have revealed great potential for clinical application. For instance, (ϩ)-JQ1 suppresses breast cancer cells (31), gastric cancer cells (32), acute myeloid leukemia cells (33), and osteosarcoma cells (13). Furthermore, I-BET151 has been shown to induce cell apoptosis in myeloma and leukemia (16,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation